Recent developments in cointegration - Katarina Jusélius (MDPI, 2018)
The Cointegrated VAR model allows the user to study both long-run and shortrun effects in the same model. It describes an economic system where variables have been pushed away from long-run equilibria by exogenous shocks (the pushing forces) and where short-run adjustments forces pull them back toward long-run equilibria (the pulling forces). In this model framework, basic assumptions underlying an economic theory model can be translated into testable hypotheses of the order of integration and cointegration of key variables and their relationships. While the latter used to be I(1), macroeconomic and financial data have recently shown a tendency for puzzling long and persistent swings around long-run equilibrium values typical of self-reinforcing feed-back mechanisms. Such persistent fluctuations are frequently indistinguishable from I(2) data, pointing to the need for new econometric solutions. In this book, many of our most distinguished scholars in the field of cointegration offer a variety of solutions to these problems by formulating new models, tests, and asymptotics more suitable for an I(2) world. Several of the papers apply these cointegration techniques to a variety of empirical problems, thereby showing how to obtain valuable information about some of the mechanisms that have generated the recent crises.
Keywords: 330